(untitled) (Bangladesh Journal of Pharmacology, 2013)
Professionalism with high moral character should be developed from the schooling time of the students. The objective of this study was to explore the professionalism of medical students. It was a cross-sectional study conducted on 108 year-I and year-II medical students of session 2012-2013 selected conveniently at UniSZA, Malaysia. Data was collected using a mixed type of validated instrument and analyzed using SPSS. Year-I and year-II were 86% and 98% respectively. Only 27% respondents were male and 73% were female. Mean professionalism scores for year-I and year-II were 175.20 and 172.91, while for male and female were 172.31 and 174.58 respectively. No significant differences observed between gender (p=0.536) and study-year (p=0.484). However, 34% year-I and 19% year-II students defined professionalism diversely while 18% and 9% were un-responded. Professionalism is a braod-concept; a burning issue worldwide. Teachers should emphasis on core elements of professionalism which are unique for all professions.